2006
DOI: 10.1038/sj.ejhg.5201722
|View full text |Cite
|
Sign up to set email alerts
|

Mutation screening of BMP4, BMP7, HOXA4 and HOXB6 genes in Chinese patients with hypospadias

Abstract: Hypospadias, one of the most common congenital abnormalities of the male external genitalia with elusive etiology, are caused by a defect in the normal development of the urethra, foreskin and ventral aspect of the penis. Evidences indicate that BMP4 and BMP7, two of those major factors in a signaling cascade involved in controlling the embryonic urethral development, play central roles in the normal development of the urethra, and that HOXA4 and HOXB6 play important roles in the development of skin in various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 19 publications
2
50
0
1
Order By: Relevance
“…Recently, mutations in several genes of HOXA cluster have been implicated in causing human disorders. Chen et al (2007) reported heterozygous sequence variants in the HOXA4 gene in Chinese patients with hypospadias. Two HOX genes, HOXB6 and HOXA4, play important roles in the epidermal development and diVerentiation of various tissues at week 10-17 of gestation (Stelnicki et al 1998;KömĂŒves et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, mutations in several genes of HOXA cluster have been implicated in causing human disorders. Chen et al (2007) reported heterozygous sequence variants in the HOXA4 gene in Chinese patients with hypospadias. Two HOX genes, HOXB6 and HOXA4, play important roles in the epidermal development and diVerentiation of various tissues at week 10-17 of gestation (Stelnicki et al 1998;KömĂŒves et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…But the low mutation rate (close to 1%) suggests that BMP4 mutations are not the major cause of this disease. Otherwise, since BMP4 has a broad range of functions in controlling multiple organogenetic processes [18,19], BMP4 mutations have been found in several diseases [2,8,35,39]. In particular, the c.485G> A (p.R162Q) mutation had also been detected in a patient with cleft lip [35].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, recent human genetic studies indicated the possible involvement of Bmp7 and Fgf(s) in the development of hypospadias. 41,42 Epithelial differentiation during the UP formation of the embryonic external genitalia (GT) One of the fundamental characters of the GT development is to develop endodermal epithelia along with GT formation, initially as CM and later forming the UP, subsequently the tubular urethra in the male GT.…”
Section: Discussionmentioning
confidence: 99%